A Quantitative SWOT Analysis of the Detailed Spatial Plan for the Nusantara Capital City East 1 Planning Area - Tiara Anvadilla (Penerbit Goodwood, 2025)
Purpose: This study examines the internal and external strategic factors shaping implementation of the Detailed Spatial Plan, known as Rencana Detail Tata Ruang (RDTR), for the East 1 Planning Area of Indonesia's new capital, Nusantara, and identifies the strategic position and development direction that the plan should pursue.Methodology: A descriptive qualitative and quantitative approach was applied through a quantitative Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, in which internal strength and weakness factors and external opportunity and threat factors were each assigned a weight and a score, multiplied to produce weighted values, and summarized in Internal Factor Analysis Summary and External Factor Analysis Summary matrices.Results: The internal factor matrix produced a total weighted score of 2.93 and the external factor matrix produced a total weighted score of 2.83, placing the plan in the aggressive, growth oriented quadrant of the internal external matrix, where internal strengths and external opportunities outweigh internal weaknesses and external threats.Conclusions: Strong national regulatory backing, the green and smart city concept, integrated spatial and transportation planning, and central government support constitute the plan's principal strengths, while financing needs, infrastructure readiness, and social and environmental risk remain the principal constraints requiring active management.Limitations: The descriptive, cross-sectional design relies on secondary documentary data and expert style weighting rather than primary survey data.Contributions: The study offers a replicable quantitative SWOT framework for evaluating detailed spatial plans in large scale, state led urban development projects.